Controle de Amaranthus spp. utilizando o potencial alelopático de Brassicas - Barbosa, Murilo Rafael (2025)
The Amaranthus genus has presented biotypes with resistance to different herbicides, making its management increasingly challenging. Alternatively, species of the Brassica genus stand out for their allelopathic potential, due to the release of chemical substances known as allelochemicals, capable of inhibiting the growth of organic plants. The present study aimed to evaluate different concentrations of dry extracts of the aerial part of canola (Brassica napus), mustard (Brassica juncea) and forage radish (Raphanus sativus) in the suppression of purple pigweed (Amaranthus hybridus), creeping pigweed (Amaranthus deflexus) and common pigweed (Amaranthus viridis) and to identify the classes of phytochemical constituents with potential allelopathic activity presented in the aqueous extract of Brassicas. The experimental design was completely randomized, in a 5x3 factorial arrangement, with five concentrations (100%, 50%, 25% and 12% and 0% as control) of dry extracts of the aerial part of Brassica species in the suppression of Amaranthus species, in four replicates. In the germination bioassay, Amaranthus species were sown in petri dishes soaked with 2 mL of each concentration and kept in BOD at 25°C and a 12-hour photoperiod, evaluating the germination percentage (%G) and the germination speed index (IVG). In the initial development bioassay, 5 ml of each extract was used on pre-germinated seeds in a container containing vermiculite, subjected to evaluation regarding hypocotyl and root length, phytotoxicity and fresh mass. A phytochemical test was performed based on qualitative reactions (color change, precipitate formation and physicochemical properties) in 2 ml samples of the crude extract of each Brassica for reducing sugars, alkaloids, anthraquinones, coumarins, steroids, flavonoids, phenols, glycosides, saponins, tannins and terpenes. An inhibitory effect on germination was observed in all concentrations of the extracts used, with greater inhibition at 50% and 100%. However, when the 12% concentration was used, there was a stimulation of the development of the weed species. The species A. deflexus was the most sensitive to the extracts, presenting the highest rate of germination inhibition. As the concentrations of the extracts increased, the IVG of the weed species was negatively affected, with a 100% reduction in the seeds exposed to the highest concentration (100%). There were no statistical differences in relation to the length of the hypocotyl, however, there was a reduction in the development of the root system of the seedlings, leading to poor development of the aerial part. The extracts induced phytotoxicity in the seedlings as the concentrations increased, culminating in necrosis, making it impossible to analyze the fresh mass. The phytochemical analysis of the extracts identified the presence of seven classes of chemical compounds: coumarin, steroid, flavonoid, phenol, glycoside, tannin and terpene. These results suggest that the different extracts used exert an allelopathic function on the germination and development of the weed species.